ANALYSIS OF THE DEVELOPMENT STRATEGY OF UNIGROUP GROUP - Dong, Guonyu (Journal of Buddhist Education and Research (JBER), 2023)
As a university-run enterprise founded by Tsinghua University 30 years ago, Unigroup Group has now become the largest comprehensive integrated circuit enterprise in China and the world's third-largest mobile phone chip enterprise. This paper analyzes Unigroup from the perspective of corporate strategy, believes that Unigroup adopts the overall related diversification strategy, combines the relevant financial indicators to analyze the strategy, and then puts forward the risk management technology and method, which is not suitable for qualitative analysis, but should take more quantitative analysis method of risk management research conclusion.